Geometric Planning of Horizontal Curved Road on Pagaralam – Tanjung Sakti – Bts Road Section, Bengkulu Province Using AutoCAD Civil 3D - Aziza Azahra; Ade Jaya Saputra (LEADER: Civil Engineering and Architecture Journal, 2023)
Road geometric planning is one of the conditions for road construction that aims to provide comfort, safety, and speed for road users. In the geometric planning of this road, the authors plan the geometric horizontal curved road on the Pagaralam - Tanjung Sakti road section at STA 0+000 - STA 2+450 located in Bengkulu Province using AutoCAD® Civil 3D. This study uses a quantitative method by taking data from Google Earth and Global Mapper. The steps in this study include terrain classification, road trace planning, horizontal alignment planning, design planning criteria, bend design, and superelevation diagram. The design results show that the Pagaralam – Tanjung Sakti road is secondary artery II, with a 2/2 TT road type. On this road section, the average slope of the Pagaralam - Tanjung Sakti road is 1.42%, and a geometric horizontal alignment designed with two bend designs using SCS (Spiral - Circle - Spiral) bend type with a radius of 550 m, Design speed (Vr) 80 km/ hours, maximum superelevation of 6% and a friction coefficient of 0.14.